Efficacy of K-wire combined with pull-out wire fixation in the treatment of acute bony mallet finger: a retrospective study - Tianhao Guo; Ruijiao Gao; Aru Zhang; Chenfei Li; Sijia Chen; Jiangbo Bai (European Journal of Medical Research)
Abstract Objectives To evaluate the clinical efficacy and safety of a novel surgical technique combining K-wire fixation with pull-out wire fixation for treating acute bony mallet finger. Methods This retrospective study included 23 patients with acute bony mallet finger treated between January 2023 and December 2024. Inclusion criteria were injuries within 4 weeks, failed conservative treatment, and fracture fragment size greater than one-third of the articular surface. Surgical details included stabilizing the DIP joint with a K-wire and supplementary fixation with pull-out steel wires to enhance stability. Postoperative outcomes were assessed using the Visual Analog Scale (VAS) score, range of motion (ROM), and Crawford criteria. Data were analyzed using SPSS software. Results The mean age of patients was 33.78 ± 10.49 years. All 23 patients experienced no complications. The mean postoperative ROM of the affected DIP joint (75.09 ± 5.32°) was comparable to the healthy side (76.83 ± 5.91°). VAS scores indicated no pain, and Crawford criteria showed excellent or good outcomes in all cases. Conclusions The combined K-wire and pull-out wire technique appears to be a safe and effective option for treating acute bony mallet finger, offering stable fixation and good early functional outcomes.